Elevation of efficacy of cancer vaccine combined with interferon and inducer of endogeneous interferon synthesis amixin - Potebnya, G.P.; Lisovenko, G.S.; Trokhimenko, N.V.; Cheremshenko, N.L.; Didenko, G.L.; Reder, A.S.; Andronati, S.S. (Experimental Oncology, 2008)
Aim: To study in vivo efficacy of combined administration of cancer vaccine (CV), interferon (IFN) and inducer of endogenous IFN — amixin. Materials and Methods: Sarcoma-37 cells were transplanted to female Balb/c mice. For the treatment, CV prepared from sarcoma-37 cells with the use of cytotoxic lectines from B. subtilis B-7025, murine IFN and amixin or their combinations were used. IFN production, content of circulating immune complexes and level of specific IgG antibodies in blood serum were determined by standard immunologic methods. Results: Using solid form of sarcoma-37 it has been shown that introduction of IFN and amixin significantly elevated efficacy of vaccine therapy, in particular index of tumor growth inhibition reach 89.2% and 81.7%. Upon combined use of CV and IFN or CV and amixin (25 mg/kg) respectively. Significant prolongation of average life span of the animals treated with CV and IFN or CV and amixin (25 mg/kg) has been registered (up to 92.7 ± 10.4 and 95.0 ± 6.2 days respectively, vs 46.8 ± 1.5 days for control animals). Conclusion: Obtained results have shown expediency of the development of schemes for combined introduction of CV with exogenous IFN, and with inducer of endogenous IFN (amixin) for elevation of efficacy of vaccine therapy.